The Relationship Between The Effectiveness of Tutor Communication and The Learning Activity of Package C Students at The PKBM Literacy Foundation - Safitri, Widia Metra; Setiawati, Setiawati (Universitas Negeri Padang, 2023)
This research motivation is the low learning activity of residents studying package C at the PKBM Literacy Foundation. This was thought to be the source by the low effectiveness of tutor communication in learning package C at the PKBM Literacy Foundation. This research aims to: 1) Give description of the tutor communication effectiveness in learning package C at the PKBM Literasi Foundation, 2) Describe the learning activity of residents studying package C at the PKBM Literasi Foundation, 3) See the correlation from the tutor communication effectiveness and the learning activeness of residents studying package C at PKBM Literacy Foundation. This research used by approach in quantitative with a type of correlational. The research population was all residents studying package C at the PKBM Literacy Foundation, totaling 38 people. The technique for sampling used stratified random sampling, taking 79% of the population, namely 30 people. The data collection technique uses a questionnaire and collection of data tools in the shape of a list of statements. The techniques for data analysis use percentages and product moments. The research results shown that: 1) the the tutor communication effectiveness in learning package C at the PKBM Literacy Foundation is categorized as poor, 2) the learning activity of students studying package C at the PKBM Literacy Foundation is categorized as poor, 3) there is a significant correlation from the the tutor communication effectiveness and active learning of residents studying package C at the PKBM Literacy Foundation.Keywords: effectiveness of tutor communication, active learning